Treasure island - Stevenson, Robert Louis (Oxford University Press Oxford, 2019)
Jim Hawkins finds a map which shows buried treasure! Can Jim stop Long John Silver from finding the treasure on Treasure Island? Ladybird Readers is a graded reading series of traditional tales, popular characters, modern stories, and non-fiction, written for young learners of English as a foreign or second language. Recommended for children aged 4+, the eight levels of Readers and Activity Books follow the CEFR framework (Pre-A1 to A2+) and include language activities that help develop key skills and provide preparation for the Cambridge English- Young Learners (YLE) exams. This Level 5 Reader is A2 in the CEFR framework and supports YLE Flyers and KET exams. The longer text is made up of sentences with up to three clauses, more complex past and future tense structures, modal verbs and a wider variety of adverbs and pronouns